Tricked - Hearne, Kevin (Iron druid chronicles, 2012)
Druid Atticus O'Sullivan has battled vengeful Norse thunder gods before, and with a little help from a Navajo trickster god Coyote,he dupes them into thinking they chopped him up in the Arizona dessert. The Navajo Coyote is not above his own mischief and Atticus is battling for survival from an unlikely source.